Evaluating Bos Impact On Aps And Neet During Demographic Bonus Era - Ramadzan Defitri Pratama (Universitas Pakuan, 2026)
The demographic bonus presents a strategic opportunity for Indonesia to boost economic growth by optimizing the participation of young people in education and the labor market. This study aims to analyze the effectiveness of the School Operational Assistance Fund (BOS FUND) at the senior high school level in increasing the School Participation Rate (APS) for individuals aged 16–18 years and reducing the proportion of NEET (Not in Education, Employment, or Training) youth aged 15–24 years. The research utilizes panel data from 38 provinces in Indonesia over the period 2021–2024 and is analyzed using the Fixed Effect Model (FEM). The results indicate that the BOS FUND has no significant impact on increasing the APS or reducing the NEET rate. Conversely, the Human Development Index (HDI) consistently has a positive impact on the APS and a negative impact on the NEET rate, while the Gross Regional Domestic Product (GRDP) per capita shows the opposite relationship. These findings suggest that the effectiveness of the BOS FUND has not been optimized without integration with human development and inclusive regional policies. Regionally based education policies and routine evaluations using panel data are recommended to support the equitable and sustainable utilization of the demographic dividend.